1999
DOI: 10.1002/(sici)1097-0231(19990215)13:3<164::aid-rcm474>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of singly charged biomolecules by electrospray ionization fourier transform ion cyclotron resonance mass spectrometry utilizing an internal standard

Abstract: The quantification of Cyclosporin A (CsA) and related biological compounds by various mass spectrometric techniques is well established. It is precisely this fact that makes the use of CsA particularly appealing as a model system in evaluating the quantitative properties of electrospray ionization coupled to Fourier transform ion cyclotron resonance mass spectrometry (ESI-FTICR-MS). Utilizing the internal standard methodology, we have generated a linear calibration curve ranging from 5-250 ng/mL CsA described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Not surprisingly, instrumental parameters that result in a τ ratio nearer to 1 generally have MQF values approaching 1. This result corroborates previous observations that accurate quantification can be achieved if two species have similar signal decay rates 29. Importantly, our results extend this observation to include a wider range of experimental conditions.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Not surprisingly, instrumental parameters that result in a τ ratio nearer to 1 generally have MQF values approaching 1. This result corroborates previous observations that accurate quantification can be achieved if two species have similar signal decay rates 29. Importantly, our results extend this observation to include a wider range of experimental conditions.…”
Section: Resultssupporting
confidence: 92%
“…Early investigations revealed that accurate quantification with FT‐ICR‐MS can be realized as long as the second isotopic beat is detected 28, 29. In a study by Gordon and Muddiman of cyclosporin A (CsA) and cyclosporin G (CsG), the authors reported coefficients of variation within ∼10% over the concentration range of 0–250 ng/ml CsA with a constant concentration of 200 ng/mL CsG, with the detection of only ten isotopic beats 29. Moreover, the relative standard deviation of the standard curve (CsA/CsG abundance ratio) was not significantly improved with the detection of more isotopic beats.…”
mentioning
confidence: 99%
“…24, 28, 77 Muddiman and co-workers demonstrated a quantitative relationship between the concentration ratios of two proteins which are 97% identical and their ESI/FTMS peak ratios as well as a linear relationship between the protein concentration and the FTMS peak intensity over ~1.5 orders of magnitude. 78 Kelleher group has developed a method called protein ion relative ratio (PIRR) where the relative ratio of MS signal intensity values were used to calculate the relative amount of modified protein forms 77 and applied it to the global assessment of the combinatorial PTMs of core histones 79 and histone H4. 80 Our group has modified such a PIRR method and quantitatively determined the phosphorylation levels in human, mouse, rat, swine, and primate cTnI 25, 2830 as well as recombinant mouse cardiac myosin binding protein C (cMyBP-C).…”
Section: Application Of Top-down Ms To Cardiovascular Researchmentioning
confidence: 99%
“…found that the signals of small proteins are suppressed by larger ones. Gordon et al reported that due to ion interaction, the spectral signal intensities do not necessarily reflect true trapped‐ion abundances 1, 5. Additional signal suppression phenomena due to the effects of measuring several peptides are reported in Schmid et al 6.…”
mentioning
confidence: 99%
“…Over the past decade or so, liquid chromatography/Fourier transform mass spectrometry (LC/FTMS) has gained increasing popularity for its high mass resolution and mass accuracy which allow for sensitive peptide identification both in LC/MS and tandem mass spectrometry (MS/MS) experiments. As the relationship between actual peptide abundance and the corresponding spectrum intensity is approximately linear,1 FTMS is also widely used in quantitative proteomics and biomarker discovery.…”
mentioning
confidence: 99%